The relationship between macroeconomic variables and foreign direct investment: Evidence from asean-5 countries - Naqiuddin Naqib, Mohamad Khairi (2020)
Foreign direct investment (FDI) is an investment which involves a long-term alliance and represents a long influential effect by the resident in a single economy. FDI stimulates economic stability and development of a country. The objective of this study is to examine the relationship between macroeconomic variables and FDI inflows in ASEAN-5 countries over the period 1988-2018. The dependent variable is FDI inflows whereas as the independent variables are economic growth, exchange rate, interest rate, inflation and trade openness. Findings from the panel unit root test reveals that all variables are stationary at 1% significance level. Based on the cointegration test, all variables are cointegrated and has a long run relationship among the variables. From the FMOLS method, this study finds that there is a negative and significant relationship between interest rate and FDI inflow. This implies that an increase in interest rate discourages foreign investment into the country. Also, there is a positive and significant relationship between trade openness and FDI inflow. Thus, an increase in trade openness attracts FDI inflows into the country. Furthermore, this study discovers that economic growth, exchange rate and inflation are not statistically significant in influencing FDI inflows in ASEAN-5 countries. Therefore, this study will provide assistance for policy makers in improving the current strategy and policies on FDI inflow